PENINGKATAN PERANAN SOSIAL MASYARAKAT DALAM PENGEMBANGAN WISATA HOT WATER BOOM SAPAN MALULUANG DI NAGARI PAUH DUO NAN BATIGO KECAMATAN PAUH DUO KABUPATEN SOLOK-SELATAN - Meisi Kurnia Sari; Rahmadani Yusran (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
Abstrak This study aims to analyze the increasing social role of the community in the development of HWB attractions. This research uses a qualitative approach with descriptive methods. The informants of this study were determined by purposive sampling technique, including the general subdivision and staffing of the department of tourism and culture Kabupaten Solok Selatan, Wali Nagari , Youth Chairperson, Community Leaders in Nagari Pauh Duo Nan Batigo Pauh Duo District Kabupaten Solok Selatan, officers, visitors, and the community around HWB attractions. techniques collection techniques carried out by observation, interview and study documentation. To test the validity of the data using source triangulation techniques. The results of this study indicate that forms of social role in developing HWB attractions provide information to the government, increase people's willingness to accept decisions, and democratize decision making. During this time, the role of the government in involving the social role of the community in the development of HWB attractions is still limited. This shows that there is no government goodwill involving the social role of the community in the development of HWB attractions. Furthermore, the supporting factors for increasing the social role of the community in developing HWB attractions are the community involved in planning HWB attractions, the willingness of the community to support the implementation of regulations made in the framework of developing HWB attractions, the involvement of the community in supporting the potential of existing tourist attractions area. While the inhibiting factor is the lack of local community initiative in managing tourist facilities, there is no permanent work for the surrounding community in HWB tourism objects. This study concludes that increasing the social role of the community in developing HWB attractions needs to be done in actively involving the social role of the community. In addition, the role of the government in involving the social role of the community is still limited, because there is no seriousness from the government in involving the social role of the community as a whole in the development of HWB tourism objects. Keywords: social role of the community and tourism development